Protecting Consumer Privacy Under Resolutions on Marketing Through Phone Calls in the UAE - Ramzi Madi (European Journal of Privacy Law & Technologies)
The UAE telecommunications market is rapidly expanding, prompting the issuance of Resolution No. 56 of 2024, which regulates marketing phone calls, and Resolution No. 57 of 2024, which addresses penalties for violations. Both resolutions take effect in mid-August 2024. Resolution No. 56 defines telemarketing and distinguishes between “marketing” and “unwanted marketing” calls. It establishes guidelines for licensed telemarketing companies and procedures to protect consumers, enhancing privacy and fair practices. Resolution No. 57 outlines administrative penalties for violations. This paper reviews the regulatory framework for telemarketing in the UAE.